Digitalisasi Komunikasi : Dinamika Teori dan Transformasi di Era Digital - Safutra Rantona; Olih Solihin; Ahmad Zakki Abdullah (Universitas 17 Agustus 1945, 2024)
The transformation of media and communication in the digital era has reshaped how people interact, share information, and build social relationships. The digitalization of communication not only introduces new platforms such as social media and the internet of things (IoT) but also impacts communication culture and social relationship patterns within society. This study aims to examine the dynamics of communication theory in the context of digitalization, understand how these concepts adapt, and explain their impact on social and cultural life. The research method used is a literature review, analyzing internationally indexed journals, along with relevant national journals. The findings indicate that digitalization encourages faster interactions and wider access to information but also presents challenges, such as discrepancies between online and real identities and the erosion of local cultural values. In conclusion, a critical understanding of the dynamics of communication theory in the digital era is essential to harness this transformation positively without overlooking existing social and cultural values.